Effects of soaking oak acorn, Quercus brantii in water on the removal of phenolic compounds and its digestibility for common carp, Cyprinus carpio - Arash Nadri; Hojjatollah Alamdari (تغذیه آبزیان, 2022)
Oak acorn is widely used as human food and animal feed. This fruit contains considerable amounts of tannin. A large amount of tannin causes a disturbance in the digestion process. The aim of this study was to reduce the amount of tannin before consuming oak acorn in the diet. Dry and de-hulled acorns were soaked in tap water (1:5; w/v) for 24, 48 and 72 h (treatments 1, 2 and 3 without water exchange and treatments 4, 5 and 6 with water change every 12 h, respectively) at 50 °C. Then acorns were dried at 60 °C for 24 h, milled and sieved with a 250-micron sieve. The highest loss of total phenolic compounds (93.34%), non-tannin phenolic compounds (95.83%) and condensed tannins (96.92%) and the highest increase in protein digestibility were observed in treatment 6 (p<0.05). Carbohydrate digestibility only in treatment 2 was higher than the control, and the increased soaking time from 48 to 72 h caused a significant decrease in the digestibility of the carbohydrate. Acorn soaking caused a significant elevation in pH in treatment 6. The pH value of digested acorn was not different from the control when water was not changed, however, it was higher than the control when water was changed. In general, treatment 6 is recommended as the best treatment in acorn processing with tap water.